2022
DOI: 10.1021/acs.langmuir.2c00252
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Concentration Gradients and Colloidal Dynamics under Electrodiffusiophoresis

Abstract: In this work, we present an experimental study of the dynamics of charged colloids under direct currents and gradients of chemical species (electrodiffusiophoresis). In our approach, we simultaneously visualize the development of concentration polarization and the ensuing dynamics of charged colloids near electrodes. With the aid of confocal microscopy and fluorescent probes, we show that the passage of current through water confined between electrodes, separated about a hundred microns, results in significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 65 publications
(130 reference statements)
0
16
0
Order By: Relevance
“…Details on the procedure that was followed to measure pH in-operando can be found in our recent publication. 40 Briefly, pH was mapped using a ratiometric fluorescent dye, 5-(and-6)-carboxy SNARF-1 (ThermoFisher, C1270). The fluorescense emission of SNARF-1 changes from yellow-orange at acidic pHs to deep red at basic pHs.…”
Section: Experimental Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Details on the procedure that was followed to measure pH in-operando can be found in our recent publication. 40 Briefly, pH was mapped using a ratiometric fluorescent dye, 5-(and-6)-carboxy SNARF-1 (ThermoFisher, C1270). The fluorescense emission of SNARF-1 changes from yellow-orange at acidic pHs to deep red at basic pHs.…”
Section: Experimental Methods and Analysismentioning
confidence: 99%
“…31,[37][38][39] In a recent work, we confirmed that electrodiffusiophoresis (EDP)-phoretic motion under diffusiophoresis and electrophoresis-was the mechanism responsible for the focusing and levitation of charged particles under uniform dc fields. 40 With the aid of confocal microscopy and ratiometric analysis, we observed that the passage of current through water induces significant pH gradients. Under those conditions, the diffusiophoretic contribution becomes large enough to balance and overcome the electrophoretic contribution.…”
Section: Introductionmentioning
confidence: 99%
“…The intent of this exercise is to study the simultaneous impact of diffusivity asymmetry and surface reactions, such as the ones present in experiments. 20–22…”
Section: Resultsmentioning
confidence: 99%
“…This relationship was systematically derived by Prieve et al 6 We acknowledge that this assumption ignores the impact of equilibrium cell potential 35,36 and also neglects higher-order effects. These effects can become important in experimental systems 20–22 where the voltage amplitude or the steady bias in the applied potential impacts the reaction rate, boundary conditions, and leading order solution. Therefore, the analysis presented here will need to be adjusted to incorporate these effects.…”
Section: Asymptotic Solution For Small Applied Potentialsmentioning
confidence: 99%
“…Achieving a detailed picture of ion transport in the solution phase under (electro)­chemically active conditions remains a major challenge that limits advances in applications ranging from solar fuel conversion and bipolar membranes to the understanding of electrophysiology. Ion transport is a multiscale problem of diffusion and electrostatics that is dictated by nanoscale solvent structuring, mesoscale impacts of local environmental structure, and microscale transport. , Typically, ion transport within electrochemical systems is probed indirectly with bulk measurements of voltage and current, leaving the species concentration profiles and transport properties to be inferred through modeling and simulations. There exist powerful techniques for probing electrode and electrolyte structure or steady-state ion distributions, and absorptive and fluorescent labels as well as Raman-active modes have been used to probe ion transport with high resolution in specific cases, , but there is an outstanding need for direct universal measurements of ion transport in native microenvironments with spatiotemporal resolution. Optical detection of electrochemical processes via voltage-induced refractive index changes at electrodes also has a long history , and has more recently been used for imaging electrochemical processes at electrode–electrolyte interfaces, electric double layer dynamics, and ion intercalation in battery electrodes .…”
mentioning
confidence: 99%